2018
DOI: 10.3390/ijerph15102117
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Suicide Risk According to Different Healthcare Professionals in Spain: A Qualitative Study

Abstract: This study analyzes the views of four groups of healthcare professionals who may play a role in the management of suicidal behavior. The goal was to identify key factors for suicide prevention in different areas of the healthcare system. Qualitative research was conducted using focus groups made up of different healthcare professionals who participated in the identification, management, and prevention of suicidal behavior. Professionals included were primary care physicians, psychologists, psychiatrists, and e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 80 publications
1
7
0
3
Order By: Relevance
“…These results point to consequences and implications for the professional work of these workers, since we do not have objective data showing a change in the trend or a lower risk of outbreaks. As observed in the results of the present study, the mental health of health workers is vulnerable to events related to their patients; they present important levels of stress and anxiety in the face of the death of the people they care for as previous research has shown [ 57 , 58 , 59 , 60 , 66 ], although in the context of the COVID-19 health crisis, it is more evident because of the short period of time in which deaths have increased significantly. However, we cannot forget the effects that the lack of PPE is having on the current health crisis, as it is the greatest predictor of anxiety in the face of the death of others.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…These results point to consequences and implications for the professional work of these workers, since we do not have objective data showing a change in the trend or a lower risk of outbreaks. As observed in the results of the present study, the mental health of health workers is vulnerable to events related to their patients; they present important levels of stress and anxiety in the face of the death of the people they care for as previous research has shown [ 57 , 58 , 59 , 60 , 66 ], although in the context of the COVID-19 health crisis, it is more evident because of the short period of time in which deaths have increased significantly. However, we cannot forget the effects that the lack of PPE is having on the current health crisis, as it is the greatest predictor of anxiety in the face of the death of others.…”
Section: Discussionsupporting
confidence: 66%
“…There is relevant information in the scientific literature about the high risk that health professionals have of presenting disorders derived from their professional practice, such as high levels of exhaustion, depression, stress, anxiety [ 57 ], some type of addiction and even post-traumatic stress disorder, which could have long-term psychological consequences [ 58 , 59 , 60 ], especially in situations of health emergencies [ 61 ]. In some cases, psychological intervention by a professional may even be necessary [ 62 , 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…This possibility of technological ubiquity creates opportunities for new forms of use and communication from these resources [3-5]. Thus, mobile apps become a possible and real alternative for the treatment of mental health problems, especially for people at risk for suicide in follow-up and treatment [6]. As Larsen et al [7] pointed out, “Apps can be especially useful for suicide prevention interventions, because of their ability to deliver support and interventions in situ and at times of crisis.”…”
Section: Introductionmentioning
confidence: 99%
“…Профилактика суицидального поведения . Профилактика СУ лежит в основе оперативной программы ВОЗ, цель которой -снизить показатели СУ на 10% к 2020 г. Важность выявления риска в профилактике СУ очевидна из того факта, что 91% из тех, кто погибает в результате СУ, в какой-то момент общались с врачами и/или медработниками в течение года до смерти, и что 66% участвуют в сетях психического здоровья, в основном в амбулаторных центрах [42].…”
unclassified
“…Prevention of SU is at the heart of World Health Organization operative programme, which aims at reducing SU by 10% by 2020. The importance of risk identification in SU prevention is evident from the fact that 91% of those who die in the result of SU have at some point communicated with doctors and/or health care providers in the year prior to death, and that 66% participate in mental health networks, mostly in outpatient centers [42].…”
mentioning
confidence: 99%